Empowerment of Female Farmers in Utilizing Household Waste as Eco Enzymes in Tumpatan Nibung Village - Lubis, Yusniar; Azwana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance environmental awareness and promote sustainable organic waste management practices among members of the Kelompok Tani Sapindo in Desa Tumpatan Nibung through eco enzyme production training. Conducted in collaboration with local agricultural stakeholders, the program targeted farmers as key agents in adopting eco-friendly practices within rural communities. The activity introduced participants to the concept, benefits, and step-by-step procedures for producing eco enzymes using organic waste such as fruit and vegetable scraps. A combination of lectures, demonstrations, and hands-on sessions ensured that participants acquired both conceptual understanding and practical competence. As a result, farmers not only learned how to produce eco enzymes but also gained the capacity to apply them as natural fertilizers and pest repellents in their agricultural routines. This initiative is expected to support environmentally sustainable farming methods and cultivate a culture of waste-to-resource transformation within the community. The program received positive responses, emphasizing the importance of empowering rural communities with simple, cost-effective, and impactful green innovations.